Does Growing Up in a High Crime Neighborhood Affect Youth Criminal Behavior? - Damm, Anna Piil; Dustmann, Christian (American Economic Review, 2014)
This paper investigates the effect of early exposure to neighborhood crime on subsequent criminal behavior of youth exploiting a unique natural experiment between 1986 and 1998 when refugee immigrants to Denmark were assigned to neighborhoods quasi-randomly. We find strong evidence that the share of young people convicted for crimes, in particular violent crimes, in the neighborhood increases convictions of male assignees later in life. No such effects are found for other measures of neighborhood crime including the rate of committed crimes. Our findings suggest social interaction as a key channel through which neighborhood crime is linked to individual criminal behavior. (JEL J13, J15, K42, R23, Z13)